Human Development Index (HDI) Rank-Order Variability - ÇİLİNGİRTÜRK, AHMET METE; KOÇAK, HABİP (SPRINGER, 2018)
In accordance with the increasing demand for information, indices are created and national and global rankings made to represent and through which to understand and build policy related to complex situations, processes and trajectories. Different indices for a single concept are also created that have advantages or disadvantages over one another or to overcome certain calculation problems. As one such, the Human Development Index (HDI) presently lists countries according to four different criteria, and remains at the heart of democratic and humanitarian recovery efforts. This type of indicator is taken as a function of past performances, with high performances being the extreme values at positively skewed distributions. Thus, the variability of each unit's repeated measures is regarded as the result of efforts made between the measurement time points (in the HDI case, of a country to promote development). However, it is assumed that the variability of the units is not homogenous. Here, it is shown that in the HDI case, high performance units show relatively low variability, whereas the middle and middle-low performance units show a high variability. Cluster analysis and Friedman test have been used to determine the characteristics of ordered country rankings. The variability of rank-order should also be taken into account besides the location on the list by clustering the countries according to HDI.
Keywords: Human Development Index; HDI rank; Order variability; Superstars theory; Friedman Chi square; Clustering; TESTS; UNCERTAINTY; METHODOLOGY; COUNTRIES; ECONOMICS